2012
DOI: 10.1208/s12249-012-9765-8
|View full text |Cite
|
Sign up to set email alerts
|

Dry Powder Inhalers: Study of the Parameters Influencing Adhesion and Dispersion of Fluticasone Propionate

Abstract: Abstract. Interactions between particles are dependent on the physicochemical characteristics of the interacting particles but it is also important to consider the manufacturing process. Blending active pharmaceutical ingredient (API) with carrier is a critical stage that determines the blend homogeneity and is the first step towards obtaining the final quality of the powder blend. The aim of this work was to study parameters that influence the interactions between API and carrier in adhesive mixtures used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…The particle-particle interaction forces have to be sufficiently strong that fine API particles can adhere with the carriers or form large agglomerates to be transported, but weak enough that they can be detached or dispersed by a deagglomeration process and thus allow the delivery of the API particles into the respiratory tracts and lungs. Therefore, particle-particle interactions play a significant role in controlling the performance of DPIs and hence many studies have been performed to explore the dependency of these interactions on particle size [7,8], material properties [9,10], particle concentration [11,12], particle morphology [13,14], particle surface roughness [15,16], storage conditions [17,18], surface area [19], density and porosity [20], and crystal form [21]. For example, Kaialy et al [7] experimentally examined the influence of the particle size of lactose carrier on the DPI performance and demonstrated that the DPI performance improved with decreasing carrier particle size.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The particle-particle interaction forces have to be sufficiently strong that fine API particles can adhere with the carriers or form large agglomerates to be transported, but weak enough that they can be detached or dispersed by a deagglomeration process and thus allow the delivery of the API particles into the respiratory tracts and lungs. Therefore, particle-particle interactions play a significant role in controlling the performance of DPIs and hence many studies have been performed to explore the dependency of these interactions on particle size [7,8], material properties [9,10], particle concentration [11,12], particle morphology [13,14], particle surface roughness [15,16], storage conditions [17,18], surface area [19], density and porosity [20], and crystal form [21]. For example, Kaialy et al [7] experimentally examined the influence of the particle size of lactose carrier on the DPI performance and demonstrated that the DPI performance improved with decreasing carrier particle size.…”
Section: Introductionmentioning
confidence: 99%
“…Le et al [17] employed a twin stage impinger to evaluate the dispersion performance at various humidity conditions and found that the FPF decreased as the relative humidity is increased. Cline and Dalby [19] found that the FPF increased with the increased surface area.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations